Research of the Geometric Characteristic of Undercutting and Limit Normal Point in Gear Geometry - Chen Ningxin (Jixie chuandong)
The undercutting phenomena and the limit normal point are two important concepts in gearing theory,design and manufacturing.Based on the different opinions about them in the current research of limit normal point and the geometry and movement characteristics of undercutting neighborhood research is not sufficient,the study on undercutting and limit normal point of the following different gears is carried out by using TCA technology,they include spur and helical involute gears,straight bevel gear,cylindrical worm-gears including I type,K type and C type worm-gear,face-milled and face-hobbed spiral bevel and hypoid gear,as well as single-enveloping and double-enveloping globoidal worm-gear.The study results show that,the sliding velocity on the undercutting line of the generated surface is not equal to zero as the traditional result but moves along the tangent of the undercutting line for most gears except for spur involute and straight bevel gears,the limit normal point is the tangent point of the undercutting line and contact boundary line indeed.